GLOBAL ENGLISH AND PUBLISHING TRENDS AT THE TURN OF THE 20TH CENTURY - KOVAČ, MIHA (Knygotyra, 2014)
The paper analyses three important social and cultural trends that reinforced reading in English in non-English-speaking countries. First, English became the lingua franca of academia, and the simultaneous explosive growth of tertiary education increased the number of English speakers globally. Second, English became the language of popular culture and, as such, now dominates global bestseller production. Third, due to the growth of Amazon and other online retailers of electronic and printed books, books in English became readily available in most non-English-speaking countries. The paper will show that in Anglo–Saxon book markets, ebooks have a different cultural role than in continental Europe and other non-English-speaking countries. In the former, ebooks are becoming a mainstream medium for reading fiction. Contrastingly, in the latter, they seem to be predominantly the domain of bilingual readers, and mainstream book markets in local languages remain heavily dominated by printed books. As a result, in contemporary book cultures, printed books and e-books coexist in a kind of dual economy. In Anglo–Saxon markets, this coexistence takes place inside the same linguistic ecosystem, while in non-English-speaking countries, for the time being, the chasm between print and digital bears a strong linguistic mark and consequently represents a new cultural phenomenon. There seem to be cognitive differences between on-paper and onscreen reading; therefore, the paper concludes with the observation that, behind this dual economy, a deeper cultural schism might be hidden, putting the academic exploration of publishing studies and the book market at the centre of a new research paradigm.KEYWORDS: global English, books, e-books, book market, publishing studies, publishing field, onscreen reading, reading.